Centrally acting drug moxonidine decreases reactive oxygen species via inactivation of the phosphoinositide-3 kinase signaling in the rostral ventrolateral medulla in hypertensive rats. Issue 5 (May 2016) - Wang, Yang-Kai; Yu, Qiang; Tan, Xing; Wu, Zhao-Tang; Zhang, Ru-Wen; Yang, Ya-Hong; Yuan, Wen-Jun; Hu, Qi-Kuan; Wang, Wei-Zhong
Abstract : Objective: Centrally acting antihypertensive action of moxonidine is a result of activation of Imidazoline-1 receptor (I1 R) in the rostral ventrolateral medulla (RVLM). Hypertension shows an increase in reactive oxygen species (ROS) in the RVLM. The present objective was to determine the phosphoinositide-3 kinase (PI3K) signaling pathway involved in the effect of moxonidine on ROS generation in the RVLM of spontaneously hypertensive rat (SHR). Methods: Wistar–Kyoto rats and SHR received intracisternal infusion (2 weeks) of tested agents which were subjected to subsequent experiments. In-situ ROS in the RVLM was evaluated by the oxidative fluorescence dye. Western blot and PCR analysis were performed to detect the expression levels of PI3K signaling pathway. Lentivirus was injected bilaterally into the RVLM for silencing PI3K signaling. Results: ROS production in the RVLM was dose-dependently reduced in SHRs treated with infusion of moxonidine (20 nmol/day), which was prevented by the I1 R antagonist efaroxan but not by the α2 -adrenoceptor antagonist yohimbine. Moxonidine pretreatment significantly blunted cardiovascular sensitivity to injection of tempol (5 nmol) or angiotensin II (10 pmol) into the RVLM in SHR. Expression levels of PI3K/Akt, nuclear factor kappa-B (NFκB), NADPHase (NOX4), and angiotensin type I receptor (AT1 R) in the RVLM were markedly decreased in SHR treated with moxonidine. Infection of lentivirus containing PI3K shRNA in the RVLM effectively prevented effects of moxonidine on cardiovascular activity and expression levels of Akt, NFκB, NOX4, and AT1 R. Conclusion: The centrally antihypertensive drug moxonidine decreases ROS production in the RVLM through inactivation of the PI3K/Akt signaling pathway in hypertension.